In situ visualization of high genetic diversity in a natural microbial community. - Amann, R (1996)
Simultaneous in situ visualization of seven distinct bacterial genotypes, all affiliated with the phylogenetically narrow group of beta-1 Proteobacteria, was achieved in activated sludge. This finding indicates that the high diversity found in the same sample by direct rRNA sequence retrieval was indeed present in this complex community. By the combination of comparative rRNA sequence analysis, in situ hybridization with fluorescently labeled, rRNA-targeted oligonucleotides and confocal laser scanning microscopy several microbial populations can be analyzed for abundance, relative spatial distribution and phylogeny directly at their site of action without prior cultivation.